2017
DOI: 10.1152/ajpcell.00187.2016
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 ion channel is a novel regulator of dermal myofibroblast differentiation

Abstract: Scleroderma is a multisystem fibroproliferative disease with no effective medical treatment. Myofibroblasts are critical to the fibrogenic tissue repair process in the skin and many internal organs. Emerging data support a role for both matrix stiffness, and transforming growth factor β1 (TGFβ1), in myofibroblast differentiation. Transient receptor potential vanilloid 4 (TRPV4) is a mechanosensitive ion channel activated by both mechanical and biochemical stimuli. The objective of this study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 56 publications
4
82
0
Order By: Relevance
“…Transforming growth factor β1 is known to induce EMT in keratinocytes . Recent evidence from our group suggests a link between TRPV4 activation and TGFβ1 signals that mediate fibroblast differentiation . Previous reports have documented that calcium signalling is involved in EMT in many cell types .…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Transforming growth factor β1 is known to induce EMT in keratinocytes . Recent evidence from our group suggests a link between TRPV4 activation and TGFβ1 signals that mediate fibroblast differentiation . Previous reports have documented that calcium signalling is involved in EMT in many cell types .…”
Section: Resultsmentioning
confidence: 86%
“…The identification of the role of specific Ca 2+ ‐permeable ion channels in the induction of EMT in the context of fibrosis and oncogenesis suggests that these channels may be appropriate therapeutic targets for control of EMT‐mediated disease progression. Our recently published reports suggested that TRPV4‐dependent Ca 2+ influx potentiates TGFβ1‐induced lung and dermal myofibroblast differentiation in response to matrix stiffness, and showed that TRPV4 KO mice were protected from bleomycin‐induced fibrosis in skin and lungs . Although TGFβ1 and matrix stiffness were shown to play important roles in EMT and fibrosis, the role of TRPV4 mechanosensing in EMT has not been reported.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations